Improvement of possibilition of verticalisation in patients whit spino bifida after surgery of the hip and knee contractures and intensive rehabilitation programme - Snela, Sławomir; Bilski, Paweł; Kwolek, Andrzej (European Journal of Clinical and Experimental Medicine, 2005)
<span style="color: #010101; font-family: Lato, sans-serif; font-size: 14px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-align: justify; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">Introduction: The main aim of the orthopedic treatment of the patients with the high level lesions in spina bifida is assuring the patients to the upright body position. When the contractures progresses and limitates patients verticalisation, surgically treatment is necessary. <span style="color: #010101; font-family: Lato, sans-serif; font-size: 14px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-align: justify; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">Material and methods: From 01.08.1999 to 31.08.2003, 19 children with spina bifida were treated at our Department. At 12 girls and 7 boys (on the average age 6,2 years) the hip flexion – abduction and knee flexion contractures were released. The hip flexion – abduction contractures occured in 15 patients (18 hips), the knee flexion contractures in 18 (24 knees), in 1 child ( 2 knees) extension contractures were observed. Before the operation 8 children stayed in bed, 9 sited in chair, 1 was verticalisated and one of them was occasionally standing in the orthoses. <span style="color: #010101; font-family: Lato, sans-serif; font-size: 14px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-align: justify; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">Results: During the surgical treatment in all patient’s the hip and knee contractures were released. The cast was removed at the hospital and the rehabiltation process and the teaching of verticalisation, standing and walking in apparatus were started. It was conducted in the cooperation with the Rehabilitation Department of our hospital. In the case of the lesion below L2 KAFO or AFO orthoses were used. In the high level of lesion T12 – L2 HKAFO orthoses were used. All the patients were verticalisated, even if the bone condition was poor. In the follow-up period (on the average 25,2 months), 15 patients were verticalisated (79%). <span style="color: #010101; font-family: Lato, sans-serif; font-size: 14px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-align: justify; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">Conclusion: Release of hip and knee contractures in children with high level lesion in spina bifida and intensive rehabilitation enables to obtain the effects of the treatment that satisfy the patients and their families.